2009
DOI: 10.1017/s1092852900023567
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Who Couldn't Stop Washing: Pathologic Grooming in Animals and Humans

Abstract: The basic science literature is replete with descriptions of naturally occurring or experimentally induced pathological grooming behaviors in animals, which are widely considered animal models of obsessive-compulsive disorder (OCD). These animal models rely largely on observed similarities between animal behaviors and human OCD behaviors, and on studies of animal pathological grooming disorders that respond to serotonin enhancing drugs. However, current limitations in assessment of complex cognition and affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 85 publications
1
48
0
5
Order By: Relevance
“…Individuals with SPD report high rates of co-occurring trichotillomania, and first-degree relatives of patients with SPD report high rates of grooming behaviors, including trichotillomania and SPD (Odlaug and Grant, 2008a,b;Wilhelm et al, 1999;Neziroglu et al, 2008). Given this overlapping familiality between SPD and trichotillomania, and that these conditions are associated with pathological habits that are difficult to suppress, it has been suggested that SPD can be viewed as a pathological grooming disorder alongside trichotillomania (Stein et al, 1994;Feusner et al, 2009;Beinvenu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with SPD report high rates of co-occurring trichotillomania, and first-degree relatives of patients with SPD report high rates of grooming behaviors, including trichotillomania and SPD (Odlaug and Grant, 2008a,b;Wilhelm et al, 1999;Neziroglu et al, 2008). Given this overlapping familiality between SPD and trichotillomania, and that these conditions are associated with pathological habits that are difficult to suppress, it has been suggested that SPD can be viewed as a pathological grooming disorder alongside trichotillomania (Stein et al, 1994;Feusner et al, 2009;Beinvenu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…64 Other common repetitive behaviors are excessive grooming (eg, combing their hair or washing their skin repeatedly), tanning (to improve their skin color or skin imperfections), reas-C l i n i c a l r e s e a r c h surance seeking (asking whether one's appearance is acceptable), excessive shopping for beauty products, changing their clothes repeatedly to find a more flattering outfit, and excessive exercise (eg, weightlifting in the case of muscle dysmorphia). 1,52,55,[64][65][66] Many BDD patients (27% to 45%) pick at their skin in an attempt to improve perceived blemishes or imperfections; however, this behavior sometimes causes observable appearance defects and can even cause severe damage such as skin infections and rupture of blood vessels. [67][68][69] Many other examples of compulsive behaviors exist, which are often idiosyncratic, such as drinking more than 3 gallons of water a day to make one's face look fuller.…”
Section: Compulsions Safety Behaviors and Avoidancementioning
confidence: 99%
“…The continual development of rodent models of diseases/disorders such as obsessive-compulsive disorder (OCD), Tourette syndrome and Huntington's disease [7,12,14,23,24,31,33] will ensure an increasing need to appropriately evaluate grooming. However, it is important for readers interested in measuring grooming to consider adopting a detailed behavioral analysis.…”
Section: Measuring Groomingmentioning
confidence: 99%